BEST PRACTICES IN HYBRID MARKETING: INTEGRATING TRADITIONAL AND DIGITAL STRATEGIES FOR MAXIMUM IMPACT - Kumar, Atul; Dalal, Bharat; Joshi, Shraddha; Rohith, Patibandla; Tripathi, Khushi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In order to develop a complete advertising strategy that more effectively engages, communicates, markets, and sells to consumers in a world where technology continues to evolve, hybrid marketing combines traditional and digital marketing approaches. The organization needs to have a hybrid overall marketing plan from a strategic point of view. This essentially means that while creating your plan, consider traditional as well as digital ways of thinking. Although embracing a hybrid marketing attitude will require intentional work at first, creating a hybrid marketing plan will become routine to you in time, particularly if you have more experience with one kind of marketing than the other. When designing a digital product, take into account how the consumer experience might be strengthened by offline connections. Likewise, in the process of generating an offline good or service, utilize the benefits of digital platforms and channels to improve consumer transaction speed, ease, and productivity. Similar offline and online channels are used by communication and equity in brands, but at various points in the customer journey, to engage and interact with customers. Digital advertising cannot reach and engage clients in the exact same manner as offline media . Using the best resources that turn out to be the most successful and generate the biggest return on investment is known as hybrid marketing. Some of the most effective hybrid advertising strategies are listed in this article.